Influence of sub-clinical endometritis on early pregnancy predictors and pro-inflammatory cytokines in circulating immune cells in dairy cows - Poit, Diego Angelo Schmidt (2021)
In the present study, our objectives were: 1) to evaluate if the expression of ISGs and proinflammatory cytokines in peripheral blood mononuclear cells (PBMCs) is affected in dairy cows with SCE compared to healthy cows; and 2) to compare the accuracy of early pregnancy predictors (ISGs and US-Doppler) in animals with and without SCE at the begging of FTAI protocol. For this , two experiments were desingned, in the Experiment 1, 30 Holstein cows, in the voluntary waiting period, between 30 and 37 days postpartum, were subbmetted a reproductive examination by transrectal palpation and ultrasonography, and all cows with no sign of uterine disease were included in the study and were subjected to an ovulation synchronization protocol (Co- synch protocol with some modifications). Seven days later (Day 0; day of expected estrus), the occurrence of SCE was diagnosed by counting the proportion of polymorphonuclear cells (PMN) in a uterine cytology sample collected by the Cytobrush technique. On days 0 and 7 (diestrus), tail blood samples were collected for isolation of peripheral blood mononuclear cells (PBMCs) and determination of gene expression by RT-PCR. After exclusion of some animals, only 12 cows were used for gene expression analysis., being 6 animals with SCE (SCE) and 6 healthy animals (NUD). Experiment 2, 50 Holstein cows that were between 40 and 55 days postpartum were used in order to evaluate the expression of target genes as well as luteal blood perfusion in animals that were diagnosed with SCE at the beginning of the fixed-time artificial insemination (FTAI) protocol. On day -10 (D0, the day of IATF) animals were subjected to a reproductive examination and for those detected without any sign of uterine disease, subjected to the Cytobrush technique as described in Exp 1. On day 21, after the IATF protocol, animals were evaluated by transrectal ultrasonography in color Doppler mode to assess blood perfusion in the corpus luteum and a tail blood sample was collected for PBMCs isolation and gene expression by RT-PCR. On day 32, a confirmatory diagnosis of pregnancy was made by B-mode ultrasonography to identify the presence of a viable embryo with heartbeat. After exclusion and confirmatory diagnosis of pregnancy, they proceeded to gene expression and luteal perfusion analyses. Then, 29 Holstein cows, were allocated to the following groups, 1) healthy and pregnant animals (NUD-P; n=7), 2) with SCE and pregnant (SCE-P; n=4), 3) healthy and non-pregnant (NUD-NP; n=8) and 4) co SCE and non-pregnant (SCE- NP; n=10). Animals with ≥ 5 % of PMN at Exp 1 and ≥ 5.5% at Exp 2 were considered with SCE, and those with ≤ 3% of PMN at Exp 1 and ≤ 2% at Exp 2 were considered without uterine disease (NUD group). The target genes selected for both experiments were ISGs (ISG15, OAS1, MX1 and IFI6) and pro-inflammatory cytokines (IL1-β, TNF- α and IFN-y). ISG15, MX1, IFI6, TNF-α , and IFN- γ expression was not altered from the presence or absence of SCE, time of assessment (Day 0 or 7), or interaction between them (P > 0.1). However, a significant effect was detected on the expression of OAS1 and IL1-β in PBMCs, being greater on Day 7 than Day 0 (P=0.02). In Exp. 2, no significant effect (P > 0.1) of gestational status, occurrence of SCE, or their interaction was observed on the expression of OAS1, MX1, IFI6, and IFN- γ (P > 0.10). However, the abundance of ISG15 and TNF- α showed a significant effect of gestational status being higher in gestating animals compared to nonpregnant animals (P=0.008 and P=0.05, respectively), while the abundance of IL1-β showed a tendency to have a higher expression in gestating animals than nonpregnant animals (P=0.06). For luteal blood perfusion, only a significant effect of gestation (P=0.01) was observed, being higher in gestating animals. In conclusion to the results of Experiment 1, the gene expression of OAS1 and IL1-β are higher during the diestrus period in dairy cows, regardless of the presence of SCE and even in the absence of conception, while the expression of ISG15, MX1, IFI6, TNF- α and IFN- γ are not altered either by the occurrence of SCE or by the moment of the evaluation. Gene expression of ISG15,IL1- β and TNF- α are greater in pregnant cows on D21 after FTAI. The abundance of ISG15 is a good early predictor of pregnancy regardless of the occurrence of SCE, while the abundance of OAS1 and CL blood perfusion are good predictor of pregnancy in cows without SCE. However, the abundance of MX1 and IFI6 were not good predictors at 21 days after FTAI.